2006
DOI: 10.1111/j.1365-313x.2006.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

Functionally redundant SHI family genes regulate Arabidopsis gynoecium development in a dose‐dependent manner

Abstract: SummaryGene duplication events, and the subsequent functional divergence of duplicates, are believed to be important evolutionary agents, driving morphological diversification. We have studied the structural and functional diversification of members of a plant-specific gene family in Arabidopsis thaliana by analysing mutant phenotypes, expression patterns and phylogeny. The SHI gene family comprises ten members that encode proteins with a RING finger-like zinc finger motif. We show that, despite being highly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
191
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(209 citation statements)
references
References 60 publications
12
191
0
6
Order By: Relevance
“…SRS4 pro ..GUS is expressed in cotyledon tips, leaf primordia, hydathodes, stipules, and lateral root primordia and weakly at the edges of petals and sepals, demonstrating that its activity largely overlaps with that of the SHI/STY genes studied previously. Kuusk et al (2006) showed that mutations in SRS4 enhanced the leaf phenotype of sty1-1 sty2-1 and, to a limited extent, that of gynoecia, confirming that SRS4 is active in leaves and buds. Additionally, transcriptome analysis (Hruz et al, 2008) reveals low levels of SRS4 transcripts in floral organs.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…SRS4 pro ..GUS is expressed in cotyledon tips, leaf primordia, hydathodes, stipules, and lateral root primordia and weakly at the edges of petals and sepals, demonstrating that its activity largely overlaps with that of the SHI/STY genes studied previously. Kuusk et al (2006) showed that mutations in SRS4 enhanced the leaf phenotype of sty1-1 sty2-1 and, to a limited extent, that of gynoecia, confirming that SRS4 is active in leaves and buds. Additionally, transcriptome analysis (Hruz et al, 2008) reveals low levels of SRS4 transcripts in floral organs.…”
Section: Resultsmentioning
confidence: 82%
“…The spatial and temporal activities of STY1, STY2, SHI, and SRS5 during plant development have been studied in detail (Fridborg et al, 2001;Kuusk et al, 2002Kuusk et al, , 2006 and were found to be largely overlapping, with some minor exceptions. Using an enhancer/promoter trap approach, Smith and Fedoroff (1995) suggested that LRP1 expression is restricted to lateral root primordia, whereas phenotypic characterizations of multiple SHI/STY mutants carrying a mutation also in LRP1, together with real-time (RT)-PCR data, revealed that LRP1 is expressed at similar sites as STY1, STY2, SHI, and SRS5 also in Arabidopsis aerial tissues .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations